They Called Us Enemy - Takei, George, 1937-; Eisinger, Justin; Scott, Steve (Steven M.); Becker, Harmony (San Diego, CA : Top Shelf Productions, 2020)
Takei's firsthand account of years spent in a Japanese concentration camp, the joys and terrors of growing up under legalized racism, his mother's hard choices, his father's faith in democracy, and the way those experiences planted the seeds for his astonishing future.
Keywords: Takei, George, -- 1937- -- Comic books, strips, etc; Takei, George, -- 1937- -- Comic books, strips, etc. -- Childhood and youth; Takei, George, -- 1937- -- Cartoons and comics; Takei, George, -- 1937-; 1850-1950; Japanese Americans -- Comic books, strips, etc. -- Forced removal and internment, 1942-1945; Actors -- Cartoons and comics; Japanese Americans -- Cartoons and comics. -- Evacuation and relocation, 1942-1945; World War, 1939-1945 -- Cartoons and comics. -- Japanese Americans; Japanese -- Cartoons and comics. -- History; Graphic novels; Japanese Americans; California -- Comic books, strips, etc. -- History -- 1850-1950; United States; California; Autobiographical comics; Nonfiction comics; Historical comics; Graphic novels; Nonfiction comics; Historical comics; Graphic novels; Comics (Graphic works); Autobiographical comics; History